Introducing Ethics: A Graphic Guide - David Robinson (Introducing (Thriplow, England), 1997)
This title traces the arguments of the great moral thinkers, Socrates, Plato, Aristotle, Hobbes, Kant and others, and brings us up to date with postmodern critics.